Dental Caries Experience and Use of Dental Services among Brazilian Prisoners - Leite Cavalcanti, Alessandro (Int J Environ Res Public Health, 2014)
This ross-sectional study involving 127 male prisoners evaluates the use of dental services and dental caries among Brazilian inmates. Data were collected by interview and clinical examination. Sociodemographic and sentencing information as well as use of dental services, self-reported dental morbidity, self-perception, and oral health impacts were investigated. The mean DMFT index value was 19.72. Of the components, the decayed component showed the highest mean value (11.06 ± 5.37). Statistically significant association was found between DMFTs with values from 22 to 32 and oral health satisfaction (p = 0.002), difficulty speaking (p = 0.024), shame of talking (p = 0.004) and smiling (p < 0.001). Regarding the use of dental services, 80% had their last dental appointment less than one year ago, with most visits occurring in prison (80%), with restorative treatment (32%), followed by dental pain (26.4%), being the main reasons for such appointments. Most prisoners used dental services provided by the prison. Although restorative treatment has been the main reason for the use of dental services, “decayed” and “missing” components contributed to the high mean DMFT index.